The Canterbury tales - McCaughrean, Geraldine (Oxford University Press, 1984)
An ilustrated retelling of Geoffrey Chaucer's famous work in which a group of pilgrims in fourteenth-century England tell each other stories as they travel on a pilgrimage to the cathedral at Canterbury.